Microorganization of ovaries and oogenesis of Haplotaxis sp. (Clitellata: Haplotaxidae) - Urbisz, Anna Z; Martin, Patrick; Chajec, Łukasz; Świątek, Piotr; LAGNIKA, Moïssou (My University, 2021)
Ovaries of Haplotaxis sp. were studied in active and nonactive states, that is, in a sexually mature specimen and in specimens outside of the reproductive period. Two pairs of ovaries were found in segments XI and XII. Especially in the nonactive state, they were in close contact with copulatory glands. Each ovary was composed of germ cells interconnected with syncytial cysts, which were enveloped by a layer of somatic cells. Within cysts each germ cell had one ring canal connecting it to the common anuclear cytoplasmic mass called a cytophore. During oogenesis clustering germ cells differentiated into nurse cells and oocytes; thus, the oogenesis was recognized as meroistic. Vitellogenic oocytes were detached from the ovaries and continued yolk absorption within the body cavity. Because recent studies have shown the variety of ovaries and germ line cyst organization in clitellates and suggest their evolutionary conservatism at the family or subfamily level, the data presented here can be valid in understanding the phylogenetic relationships among Clitellata. In this context, ovaries found in Haplotaxis sp. resembled those of the “Tubifex” type. “Tubifex” ovaries are characteristic for numerous microdrile taxa (tubificines, limnodriloidines, propappids, lumbriculids, and leech-like branchiobdellids) and can be regarded as the primary character for these Clitellata in which germ-line cysts are formed during early oogenesis. As the family Haplotaxidae is currently considered to be paraphyletic and the species studied here belongs to Haplotaxidae sensu stricto, our results support the close relationship of Haplotaxidae sensu stricto to the clade consisting of Lumbriculidae, Branchiobdellida, and Hirudinida, in which lumbriculids are sister to the latter two.
Keywords: Annelida; cyst; germ-line; nurse cells; oocyte